(untitled) (Research, Society and Development, 2018)
The purpose of this paper is to analyze the urgency of the recomposition of the National Forum of Education (FNE) proposed by Ordinance nº. 577 of 2017. It shows a close relationship established in the ethical-political contradiction of business thinking and its representatives, in addition to revealing the proximity of the relationship between Ordinance No. 577/2017 and the Decree of the Federal Executive of April 26, 2017, which changes the schedule for holding the National Education Conference (CONAE). Bibliographical research and document analysis, in the critical-dialectical perspective, led this research. The results point to a double regression in the basic education of the country, by expanding privatist interests and by restricting the role of civil society and its representative entities in the social control of educational policies.